Analisis Kualitas Pengembangan Profesional Berkelanjutan Di Bidan Widiarti Kiangroke - Jaoza, Salsabila Nuril; Fitria, Ida Jalilah (STIM-LPI Makassar, 2025)
Continuing professional development is a continuous process to improve the abilities, knowledge, and skills of midwives in providing quality services. This study employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation studies. Informants included primary midwives, assistant midwives, doctors, midwife assistants, patients, administration, and cleaning staff. Interviews focused on their perceptions and experiences regarding the implementation of continuous professional development and its impact on midwifery practice. The results showed that continuous professional development had a positive impact on improving knowledge, skills, confidence, and professional attitudes in managing various childbirth situations. Midwife Widiarti actively participated in training, seminars, and routine evaluation activities. This had a positive impact on patient satisfaction, the safety of medical procedures, and collaboration among staff. However, it was found that aspects of family planning (FP) services still needed improvement in terms of access and availability. Overall, Midwife Widiarti's practice has demonstrated a concrete effort in building a sustainable professional work culture and can serve as an example for other midwifery practices.